The effect of knowledge spillover on productivity: Evidence from manufacturing industry in Indonesia - Irvan Kuswardana; Nachrowi D. Nachrowi; Telisa Falianty; Arie Damayanti (Cogent Economics & Finance, 2021)
In this study, we analyze the effect of knowledge spillover on productivity in the Indonesian manufacturing industry from 2010 to 2014 using inter-sectoral linkages and inter-regional linkages. For the first time in the literature, we apply an input-output table and geographic distance between regions as the weight matrix in spatial econometric estimation to measure the productivity spillover. We find that: (1) productivity spillover from transactions of intermediate goods in vertical linkage (customer-supplier) is dominated by inter-industry downstream and intra-industry upstream; (2) the adoption of foreign technology by domestic firms through imported materials is more vital than foreign direct investment; (3) productivity spillover created from capital-intensive industries is higher than that from labor-intensive industries; (4) in productivity spillover flows through inter-regional spillover and intra-regional spillover, the latter creates higher productivity spillover than the former. This implies that the shorter the geographic distance, the narrower the technology gap; (5) investments in human capital and physical capital are a prerequisite for absorbing technology and thus essential absorptive capacity factors for firms/industries/regions as they narrow down the technology gap between developing and advanced firms/industries/regions.
Keywords: 330; inter-sectoral; linkage; productivity; spatial; spillover